Comparison of Propolis and Calcium Hydroxide in terms of Mineralization and Cytotoxicity Using Dental Pulp Stem Cells - Ahangari, Zohreh; Tabatabaei, Fahimeh S.; Hakimi, Narjes; Jalili, Maryam; Ghodsian, Behnaz; Nakhaee, Mahdieh (Journal of Dental School, 2019)
Objectives: This study aimed to compare the in vitro cytotoxic activity of propolis, a bioactive material made by the honeybee, and calcium hydroxide (CH) and their effect on formation of mineralized nodules by human dental pulp stem cells (HDPSCs). Methods: In this in vitro study, HDPSCs were obtained from the Cellular and Molecular Oral Biology Laboratory of School of Dentistry, Shahid Beheshti University of Medical Sciences. In order to evaluate the proliferative effect of propolis and CH, HDPSCs were incubated with different concentrations of propolis (0-32mg/mL) and CH (0-4.8 mg/mL). Twenty-four and 48 hours later, the methylthiazolyl diphenyl-tetrazolium bromide (MTT) assay was carried out to evaluate the proliferation potential and viability of HDPSCs treated with propolis and CH. The effect of propolis and CH on mineralization of HDPSCs was assessed by alizarin red staining. Results: The MTT assay revealed that propolis at its highest concentration caused the greatest proliferation after 24 and 48 hours. Alizarin test showed that the lowest concentrations of CH and propolis at 14 days induced the formation of calcium nodules but at 21 days, propolis was deposited on the cells and calcification was not well recognizable. Conclusion: Propolis led to higher cell vitality at all concentrations in comparison to CH. However, due to its deposition on the cells, its effects on mineralization at 48 hours could not be determined.